The Use of Semantic Mapping to Improve The Students’ Vocabulary in Seventh Grade Students of SMP NU Sabilunnaja Babat - Mukhtarul Anam; Anik Hidayanti (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aims to determine how semantic mapping can increase students' vocabulary in seventh grade students of SMP NU Sabilunnaja Babat. The method used in this research was the classroom action research (CAR). The instruments used in collecting data were tests and observation sheets. Based on the data that score, the result of calculation based on formula shown result average preliminary test were 61. The resulting test of Cycle 1 was 71, and the last Cycle was 86. The score of average on every Cycle is reached to criteria of success. Using semantic mapping can improve the seventh-grade students of SMP NU Sabilunnaja. The result of observation in Cycle 1 with 24 students they are 19 (79,16%) students be active and 5 (20,83%) students passive, and the result of observation in Cycle 2 was 22 (91,66%) students active than 2 (8,33) students passive. This study concluded that semantic mapping could teach vocabulary. The researcher suggests to the teachers that teaching vocabulary can use semantic mapping. Keywords: Vocabulary, semantic mapping